Analyzing the impact of digital classrooms on mathematics calculation skills and learners’ motivation - Oumelaid, Najim; El Boukari, Brahim; El Ghordaf, Jalila (Journal of Education and Learning (EduLearn), 2025)
This paper presents the findings of a comprehensive experimental study examining the impact of computer-assisted instruction (CAI) compared to traditional teaching methods on learner performance and motivation in mathematics education. The study, conducted with 80 first-year college learners from a primary school in Morocco, aimed to assess the effectiveness of CAI in enhancing learning outcomes and promoting learner engagement. Through pre- and post-intervention tests, the study evaluated mathematical calculation abilities, while questionnaires were utilized to measure changes in learner motivation. The results revealed significant improvements in both mathematical performance and motivation within the experimental group following the CAI intervention. In contrast, minimal changes were observed in the control group receiving traditional instruction. These findings underscore the potential of CAI to not only improve academic achievement but also foster greater motivation among learners in mathematics education. The study contributes valuable insights to the ongoing discourse on technology integration in education, emphasizing the importance of innovative instructional methodologies in optimizing learner learning experiences and outcomes.